Coordination-driven self-assembly of a series of dinuclear M2L2 mesocates with a bis-bidentate pyridylimine ligand. Issue 22 (14th May 2021) - Chainok, Kittipong; Jittirattanakun, Siripak; Theppitak, Chatphorn; Jiajaroen, Suwadee; Puangsing, Praifon; Saphu, Watcharin; Kielar, Filip; Dungkaew, Winya; Rungtaweevoranit, Bunyarat; Sukwattanasinitt, Mongkol
Abstract : The metallosupramolecular M2 L2 mesocate was rationally designed and synthesized. This material shows exceptionally high MeOH vapour uptake at STP with good recyclability and also exhibits CO2 adsorption at room temperature and 1 bar. Abstract : Four isostructural dinuclear M2 L2 mesocates of the general formula [M2 (NCS)4 (L)2 ]·4.5MeOH (1M ; M = Mn, Fe, Co, Zn) were constructed by using the coordination-driven self-assembly of the [M(NCS)2 ] precursor and the flexible bis-bidentate pyridylimine Schiff base ligand L (L = 4, 4′-(1, 4-phenylenebis(oxy))bis( N -(pyridin-2-ylmethylene)aniline). The centrosymmetric M2 L2 mesocate forms through the side-by-side coordination of two L ligands to a pair of M(ii ) ions. The mesocates exhibit a reversible temperature induced desolvation–solvation behavior without losing their structural integrity. The activated 1Co, as the representative M2 L2 mesocate, shows an exceptionally high MeOH vapour uptake capacity of 481.9 cm 3 g −1 (68.8 wt%) at STP with good recyclability. Notably, it also exhibits CO2 adsorption with an uptake capacity of 20.2 cm 3 g −1 (3.6 wt%) at room temperature and 1 bar.